Recent Advances and Innovations in SAP S/4HANA Cloud and SAP BTP and SAP AI: Integration Strategies and Latest Developments - Sravan Kumar Nendrambaka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive analysis of recent advancements and integration strategies in SAP S/4HANA Cloud and SAP Business Technology Platform (BTP), examining their combined impact on enterprise digital transformation. The article explores the architectural evolution of these platforms, focusing on their core components, integration frameworks, and deployment flexibility across on-premises, cloud, and hybrid environments. Through detailed examination of industry-specific implementations in retail, healthcare, and manufacturing sectors, the article demonstrates how organizations leverage these platforms to achieve operational excellence and innovation. The article investigates the technical infrastructure of SAP BTP, including its Platform-as-a-Service capabilities, development environments, and artificial intelligence integration, while evaluating the business intelligence and analytics capabilities that enable real-time decision-making. Special attention is given to the commercial models and economic implications of adopting these technologies, including consumption-based and subscription pricing strategies. The article concludes by identifying emerging trends and future developments, providing valuable insights for organizations planning or executing their digital transformation initiatives. This comprehensive article analysis reveals how the integration of SAP S/4HANA Cloud and BTP creates a robust foundation for enterprise innovation, while highlighting critical considerations for successful implementation and adoption.